2020
DOI: 10.3168/jds.2020-18504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lonicera japonica extract on lactation performance, antioxidant status, and endocrine and immune function in heat-stressed mid-lactation dairy cows

Abstract: Here, we examined the effects of Lonicera japonica extract (LJE) on lactation performance, antioxidant status, and endocrine and immune function in heatstressed mid-lactation dairy cows. Twenty-four healthy Chinese Holstein mid-lactation dairy cows, all with similar milk yield (30.0 ± 1.0 kg/d), parity (2.5 ± 0.3), and days in milk (105 ± 5 d) were allocated to 4 groups using a randomized complete block design: a negative control group (without LJE supplementation; CON) and groups that received LJE at 14, 28, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…An automated biochemistry analyzer (Hitachi 7080, Tokyo, Japan) was used to measure serum biochemical parameters: the serum total protein (TP), albumin (ALB), triglyceride (TG), total cholesterol (TC), high-density lipoprotein-cholesterol (HDL), low-density lipoprotein-cholesterol (LDL), urea nitrogen (UREA), and glucose (GLU) concentrations; and the serum aspartate aminotransferase (AST), and alanine transaminase (ALT) activities ( Sun et al, 2017 ; Ma et al, 2020 ). The serum concentrations of mineral elements (Ca, Cu, P, Zn, Mg, and Fe) were measured using inductively-coupled plasma optical emission spectroscopy (ICP-OES, PQ 9000, Analytik Jena, Jena, Germany), as described in the Chinese National Standards (GB 5009.268, China, 2016) and as reported previously ( Wei et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…An automated biochemistry analyzer (Hitachi 7080, Tokyo, Japan) was used to measure serum biochemical parameters: the serum total protein (TP), albumin (ALB), triglyceride (TG), total cholesterol (TC), high-density lipoprotein-cholesterol (HDL), low-density lipoprotein-cholesterol (LDL), urea nitrogen (UREA), and glucose (GLU) concentrations; and the serum aspartate aminotransferase (AST), and alanine transaminase (ALT) activities ( Sun et al, 2017 ; Ma et al, 2020 ). The serum concentrations of mineral elements (Ca, Cu, P, Zn, Mg, and Fe) were measured using inductively-coupled plasma optical emission spectroscopy (ICP-OES, PQ 9000, Analytik Jena, Jena, Germany), as described in the Chinese National Standards (GB 5009.268, China, 2016) and as reported previously ( Wei et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…It indicated that Honeysuckle has good anti-inflammatory properties [ 14 ]. An experimental study showed that adding Honeysuckle extract could reduce the concentration of IL-2 in the middle stage of heat stress; it indicated that Honeysuckle extract had effects on the antioxidant status and immune function of cows [ 27 ]. Furthermore, there is evidence that β -carotene can reduce skin inflammation by inhibiting the expression of inflammatory factors and reducing the activity of MMP9 in the ox-AD mouse model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarized the application of L. japonica (extract) in animal production in recently years. It showed that these studies mainly focus on pigs ( Liu W. et al, 2016 ), beef cattle ( Fu et al, 2016 ; Yejun et al, 2019 ), dairy cows ( Ma et al, 2020a , b ; Zhao et al, 2020 ), broiler ( Müştak et al, 2015 ), laying hens ( Long et al, 2018 ), Penaeus monodon ( Chen et al, 2013 ), grass carp ( Meng et al, 2019 ), and olive flounder ( Dharaneedharan et al, 2016 ).…”
Section: Application Of L Japonica In Animal Productionmentioning
confidence: 99%
“…Moreover, in vitro studies showed that L. japonica extract could regulate rumen fermentation and reduce methane production by inhibiting the growth of methanogenic bacteria ( Huang et al, 2019 ; Yejun et al, 2019 ). Studies on dairy cows showed that dietary supplementation of L. japonica extract could relieve heat stress of dairy cows by improving immune and antioxidant capacity ( Ma et al, 2020a , b ; Gao et al, 2021 ), enhancing anti-inflammatory activity ( Zhao et al, 2020 ). Meanwhile, L. japonica extract can improve rumen microbial diversity and improve rumen fermentation capacity ( Tang et al, 2018a ).…”
Section: Application Of L Japonica In Animal Productionmentioning
confidence: 99%
See 1 more Smart Citation